IPRs Regime and Economic Development - Parkash, Om; Bhatia, Rajiv; Sharma, Renu (Gyan Management Journal, 2007)
Several developing countries have undertaken significant steps for strengthening of their Intellectual Property Rights (IPRs) regime. In this global economy, the creation of knowledge and its adaptation to product design and production techniques are increasingly essential for commercial competitiveness and economic growth. The crucial question is whether or not the extension of Intellectual Property Rights regime assists developing countries in obtaining access to such technologies, and whether and how Intellectual Property Rights protection can help developing countries to achieve their economic and social development and to reduce poverty.
Keywords: IPRs Regime; Economic Development; Intellectual Property Rights